PERSPEKTIF K.H. AHMAD DAHLAN DALAM MENDIRIKAN MUHAMMADIYAH - Fadilla, Nurul; Saragih, Hendra; Ardianti, Siti (UIN Sumatera Utara, 2021)
Abstract: K.H. Ahmad Dahlan was born in Kauman Yogyakarta (1285 H coincides 1868 AD) - and died on February 23, 1923 (55 years old) and buried in Karangkajen, Yogyakarta. By the Government of Indonesia, he was appointed as a Hero of Indonesian Independence with Decree No. 657 of 1961.Muhammad Darwisy is the childhood name of Kyai Haji Ahmad Dahlan. He was born on August 1, 1868 Yogyakarta and died at the age of 54 on February 23, 1923. He is the founder of one of the largest organizations in Indonesia, Muhammadiyah. He is also a scholar and one of the figures of Islamic renewal in Indonesia. In general, the driving factor for the birth of Muhammadiyah stems from several social, religious, and moral anxieties and concerns. This social anxiety occurs due to the atmosphere of ignorance, poverty, and backwardness of the people. the background of the establishment of the Muhammadiyah Association can be divided into 2 causal factors, namely the Individual factor of KH. Dahlan (Subjective) and External Factors (objective). The values that can be exemplified from Kyai Ahmad Dahlan, especially in the world of education are very broad. However, some values can be taken as supporting the lives of mankind in the field of education, such as having to be a person who never gives up and does not delay something that is being studied.Keywords: Life History, Muhamamdiyah Background, and Character Value.